Qizhu Yuling prescription in the prevention of postoperative metastasis and recurrence of esophagus cancer: study protocol for a randomized, double-blind, placebo-controlled, multicenter clinical trial - Kong, Miao; Xu, Bowen; Zhu, Guanghui; Wang, Xinmiao; Kuang, Ziyu; Sun, Qianhui; Liu, Kexin; Wang, Zilin; Zhang, Ying; Li, Jie (Frontiers in Oncology, 2025)
BackgroundEsophageal cancer (EC) is a malignant tumor with a high recurrence and metastasis rate and poor prognosis. In 2024, China ranked first in the world in terms of new EC cases and deaths. Surgery is the main treatment method for EC, but the clinical difficulty is how to prevent recurrence and metastasis after surgery. Traditional Chinese medicine as a complementary therapy has played an important role in this regard. Preclinical studies have confirmed that Qizhu Yuling Prescription (QZYLP) has anticancer effects, reduces treatment side effects, and improves quality of life, except for the lack of long-term prognostic results. Therefore, this study aims to investigate whether QZYLP can reduce the recurrence and metastasis rates of EC after surgery, improve disease-free survival (DFS), prolong overall survival, and observe the safety of the drug.MethodsThis study is a multicenter, randomized, double-blind, placebo-controlled clinical trial. It seeks to enroll 310 patients from 10 hospitals who have completed adjuvant therapy following R0 surgery for esophageal squamous cell carcinoma without recurrent metastasis. Using a center-randomized design, participants will be assigned to the control group (n=155, receiving placebo treatment) or experimental group (n=155, receiving QZYLP granules treatment). Treatment will last for 6 months, with follow-up every 3 months after the final treatment or endpoint event, continuing for up to 3 years postoperatively. The primary outcome measured is DFS at 1 year postoperatively. Secondary outcomes included indicators related to prognosis, fat distribution, peripheral blood inflammation, tumor markers, and quality of life scales.DiscussionThis study aims to further clarify the efficacy and safety of QZYLP in preventing postoperative recurrence and metastasis of EC, and to explore the mechanism of action. The results of this study will provide high-quality evidence for the participation of TCM in the comprehensive treatment program of EC, and improve the precise diagnosis and treatment system of TCM in EC.Clinical trial registrationClinicalTrials.gov, identifier NCT05626309.